Memahami Dampak Pengendalian Diri terhadap Komitmen Latihan Melalui Mediasi Burnout di Kalangan Atlet Perguruan Tinggi - Mayang Salsabila; Miftakhul Jannah (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. Self-control is a crucial factor in influencing college athletes' training commitment. In this study, burnout serves as a mediating variable for the influence of self-control on training commitment. Given the importance of training commitment in the training process, appropriate interventions are needed for college athletes to develop self-control and overcome burnout. This study aims to predict the influence of self-control on training commitment with burnout as a mediating variable. Materials and methods. A quantitative approach was chosen for this study, and questionnaires were completed by 123 college athletess university in Surabaya. Participants filled out a questionnaire containing the Brief Self-control Scale (BSCS), the Athlete Burnout Questionnaire (ABQ), and the Athlete Commitment Instrument (ACI). Data analysis was conducted using the Structural Equation Modeling (SEM-PLS) technique. Based on the results of the mediation test, it was found that p = 0.009, which means that burnout has a mediating effect on the influence of self-control on training commitment. Results. This means that college athletes with high self-control will have high training commitment with a tendency toward low burnout levels. College athletes with good self-control will maintain training commitment and manage any burnout they experience. The results of this study can contribute to the relevant parties by examining the interventions used to conduct exercises to minimize burnout. Conclusions. Additionally, these new findings recommend further research to explore the type of intervention appropriate for the intensity and volume of exercise. It is concluded that burnout is able to mediate the influence of self-control on training commitment.